Violência doméstica contra a mulher trabalhadora negra e não negra: a/o assistente social trabalhadora/or assalariada/o pelo estado capitalista diante da miséria do patriarcado - Pereira, Alana Andreia (2022)
Black working women carry within themselves the contradictions established by the Brazilianstyle capitalist sociometabolism due to their experience of worforce exploitation and others most diverse oppressions. By understanding the heterogeneity of the working class, it has become evident that the black working women condenses the turmoil between class, ethnic-racial, sexual and intergenerational social relations, all centrally alienated issues, in the rumble of the Brazilian particularity. When talking about black working women, studying eugenic theories and the criticism of whiteness carried out by anti-racist struggles, several elements became explicit, for example, in the deception of “being white” in contrast to “being black”, “being ‘negra’” (term in portuguese), “being be parda” (term in portuguese). I prioritize the use of the category black and non-black working women, since the Brazilian particularity still requires nuances to portray this parda (term in portuguese) population that feels lost and concealed, not only by racism, but also by the hetero-identification stands and phenotypic characteristics. Researching violence against women implies giving centrality to the black working women as a subject that occupies the top of the indexes of women in conditions of violence perpetrated by men, with whom they have had sexual relations, which are condemned to sell their workforce as they can to survive, or with some luck and pinches of “empowerment”, to live. The theoretical course included: from the patriarchy of misery to capitalist molds, followed by the misery of patriarchy in neoliberal times; and the ways in which feminisms come to Social Work in the democratic court and their contributions to Marxist socialist feminism, especially the black feminism, the materialist feminism, the feminism from the “theory” of social reproduction and socialist Marxism. In addition, categories such as ideology and the bourgeois ideological way, such as oppressions, its ideologies of fighting violence against women (in this case the ideology "empowerment"), were discussed. An analysis of the social assistance policy was also carried out; a review of the historical syncretism of social work and the insertion of “empowerment” as a strategy of therapeutic practice. From this, I return to the professional performance of social work with black and non-black workers under conditions of violence, highlighting the professional category as salaried workers by the capitalist State, really subsumed to the capital as salaried workers. As a result, it is essential to highlight the importance of deepening the category of social reproduction from the contributions of Lise Vogel; and I also recognize the centrality of the work category, but distance myself from materialist feminism, while not working with determinant social markers, considering dialectics as an essential category for analysis. The lack of research linked to reality was made explicit to better direct the struggles and achievements for the Brazilian working class. Considering not only to break cycles of violence for a supposed “culture of peace”, but to build structuring policies linked to struggles with the horizon of social revolution proposed by the most radical anti-capitalist, anti-racist, anti-patriarchal, anti-heteronormative struggle. Finally, I permeate what are the limits, possibilities and challenges of the professional work of social workers, passing through the criticism of conditional groups, crafts and immediate responses to the professional routine